ANALISIS IMPLEMENTASI SEGMENTING, TARGETING DAN POSITIONING TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI ABG SIDOARJO - Sudarso, Satrio (Jurnal Riset Entrepreneurship, 2022)
The discussion that becomes the background in this research is the development of the culinary business that is increasingly rapidly increasing so that business competition is increasing, so the right marketing strategy is needed. In order for culinary businesses to achieve the expected sales targets, companies must pay attention to strategies that influence purchasing decisions, including the right STP (segmentation, targeting, and positioning) strategy in order to win the competition in the market. This research is a quantitative research method with causality research techniques. The independent variables of this study are segmenting (X1), targeting (X2), positioning (X3) with the dependent variable is purchasing decisions (Y). The population in this study are all consumers who make purchases at Kedai ABG. The sample used in this study were 50 respondents. The sampling technique used is non-probability sampling with incidental sampling method. The data collection instrument used was a questionnaire. The analysis technique used is multiple linear regression analysis and hypothesis testing using SPSS software for windows. The main results of this study are (1) segmentation has a positive effect and has a significant influence on purchasing decisions, (2) targeting has a positive effect and has a significant influence on purchasing decisions, (3) positioning has a negative effect and has no significant effect on purchasing decisions, (4) segmenting, targeting and positioning together (simultaneously) have a significant effect on purchasing decisions.